2007
DOI: 10.1002/humu.20522
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale population-based metabolic phenotyping of thirteen genetic polymorphisms related to one-carbon metabolism

Abstract: Several polymorphisms of genes involved in one-carbon metabolism have been identified. The reported metabolic phenotypes are often based on small studies providing inconsistent results. This large-scale study of 10,601 population-based samples was carried out to investigate the association between a panel of biochemical parameters and genetics variants related to one-carbon metabolism. Concentrations of total homocysteine (tHcy), folate, vitamin B(12) (cobalamin), methylmalonic acid (MMA), vitamin B(2) (ribofl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
123
4
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(139 citation statements)
references
References 77 publications
(67 reference statements)
11
123
4
1
Order By: Relevance
“…Previously published data show that the TCN2 776 G allele is associated with decreased transcription and decreased concentrations of cellular and plasma transcobalamin, the carrier protein that delivers vitamin B 12 to cells [36]. This suggests [36][37][38] in addition to increased MMA [39] and Hcy concentrations [37,40]. Previous studies, however, did not find an association between this polymorphism and either holotranscolbalamin [41] or Hcy [38,42].…”
Section: Discussionmentioning
confidence: 95%
“…Previously published data show that the TCN2 776 G allele is associated with decreased transcription and decreased concentrations of cellular and plasma transcobalamin, the carrier protein that delivers vitamin B 12 to cells [36]. This suggests [36][37][38] in addition to increased MMA [39] and Hcy concentrations [37,40]. Previous studies, however, did not find an association between this polymorphism and either holotranscolbalamin [41] or Hcy [38,42].…”
Section: Discussionmentioning
confidence: 95%
“…Dekou et al 10 and Fredriksen et al 15 have both reported that CBS 844ins68 carriers have fasting homocysteine levels that are modestly but significantly lower than those of noncarriers, although others have found no statistically significant difference in homocysteine levels between carriers and noncarriers. 16 -19 Interestingly, some studies in which carrier status did not influence fasting homocysteine found that after methionine loading, used experimentally to raise homocysteine concentrations and induce the CBS-mediated transsulfuration pathway, the CBS 844ins68 allele is associated with decreased homocysteine levels.…”
Section: Discussionmentioning
confidence: 99%
“…20 Others have reported effects attributable to the 699C4T and 1080C4T polymorphisms; however, these are both silent changes that themselves are unlikely to have a direct effect indicating the possibility of linkage disequilibrium with as yet unknown transcriptional control elements. 15,23 Two reports, a European-wide study 9 and a subsequent study from the United Kingdom, 10 have suggested that the CBS 844ins68 allele may counterbalance the homocysteine-raising effect of the MTHFR 677TT genotype, although these findings were not replicated in a subsequent UK study. 19 Our results, derived from a Northern Irish sample, support the reports that homocysteine levels in MTHFR 677TT homozygotes who carry the CBS 844ins68 Figure 2 Median serum folate levels by cystathionine b-synthase (CBS) 844ins68 genotype within each 5,10-methylenetetrahydrofolate reductase (MTHFR) 677C4T genotype class.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly, the two MTHFR mutant homozygotes (TTCC) never occur together, which appears to be the situation globally, as large scale studies by Fredriksen et al (2007) in Norway and a meta-analysis by Martinez-frias (2008) also fail to get this combination. It is reasonable to conclude that this genotypic combination is under strong selection pressure (also see Callejon et al, 2007).…”
Section: Discussionmentioning
confidence: 99%